Why do countries request assistance from International Monetary Fund? An empirical analysis - Ifrah Siddique; Muhammad Azmat Hayat; Muhammad Zahid Naeem; Abdullah Ejaz; Cristi Spulbăr; Ramona Birau; Toni Calugaru (Journal of Risk and Financial Management, 2021)
This paper investigates the determinants behind persistent and prolonged stays under the International Monetary Fund (IMF) program and its effectiveness, using panel data consisting of 70 countries that have requested IMF support multiple times, during the period 1980-2018. By employing panel survival analysis, we conclude that weak economic indicators, e.g., current account deficit, high debt service ratio, low GDP, are the main reasons that force a country to reach out to the IMF support program. We further extend our analysis to investigate the effectiveness of the IMF program by dividing our sample into two groups, based on income level. To overcome the issue of endogeneity, we implement the panel instrumental two-stage least squares (2SLS) fixed-effect model. In the light of our analysis, we find a contemporaneous positive impact of the IMF fund program on the economic growth of upper middle-income countries, while, for low-income countries, its contemporaneous impact is insignificant, but becomes visible over time.
Keywords: 330; endogeneity; IMF; low- and upper middle-income countries; panel survival analysis